Hot electrons induced degradation in lattice-matched InAlN/GaN high electron mobility transistors. (January 2016) - Ren, Jian; Yan, Dawei; Mou, Wenjie; Zhai, Yang; Yang, Guofeng; Gu, Xiaofeng
Abstract: In this paper, lattice-matched Pt/Au-In0.17 Al0.83 N/GaN high electron mobility transistors (HEMTs) were fabricated, and the degradation characteristics of the gate leakage current were investigated by drain-to-source voltage ( V DS ) step-stress measurements under the ON, semi-ON, and OFF stress conditions and at different temperatures, respectively. It is found that, (1) there exists a critical value of V DS, beyond which the gate leakage current begins to increase significantly; and (2) the degradation of gate leakage current has a positive temperature coefficient, indicating that high temperature can accelerate the degradation. A hot electron model is used to explain the experimental results, emphasizing that the hot electrons from the channel can induce additional negatively charged defects at the InAlN/GaN interface, which can increase the local electrical field and introduce a thinner surface barrier and finally enhance the vertical leakage current component, leading to the current degradation. Highlights: We fabricate lattice-matched Pt/Au-In0.17 Al0.83 N/GaN HEMTs. A critical V DS is found beyond which InAlN/GaN HEMTs begin to degrade. V GS and temperature play important roles for the degradation. A hot electron model is used to explain the degradation.